ANALISIS KUALITAS LAYANAN JARINGAN 4G LTE MENGGUNAKAN METODE WALK TEST DAN PENGUKURAN QOS (QUALITY OF SERVICE) DI SAMARINDA CENTRAL PLAZA - Tri Duwi Pramudito; Wawan Joko Pranoto; Abdul Hallim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the quality of 4G LTE network services at Samarinda Central Plaza (SCP) using the Walk Test method and Quality of Service (QoS) measurements for three major providers: Telkomsel, XL Axiata, and Indosat. Measured parameters include Reference Signal Received Power (RSRP), Signal-to-Interference-plus-Noise Ratio (SINR), Reference Signal Received Quality (RSRQ) using the G-NetTrack Pro application, and throughput, delay, and packet loss using the Wireshark application. The results indicate that Telkomsel exhibited the most stable RSRP performance within the "Good" category. XL Axiata excelled in throughput and SINR, while Indosat demonstrated significant performance variations, particularly in SINR and throughput. Environmental factors such as visitor density, building materials, and the location of Base Transceiver Stations (BTS) affected network quality at SCP. All providers recorded low delay values and minimal packet loss, reflecting reliable networks overall. Based on the findings, it is recommended that Telkomsel enhance network capacity in high-traffic areas, XL Axiata expand its excellent signal coverage, and Indosat improve connection stability. Additionally, collaboration between service providers and SCP management is suggested for installing signal-boosting devices in indoor areas to ensure optimal network quality, especially in high-activity zones. This study provides significant contributions to improving mobile network service quality in crowded environments like SCP.